Pesquisa de Campylobacter jejuni e Campylobacter coli em abatedouros de aves - Cortez, Ana L.L. (2006)
The genus Campylobacter is of great importance to public health because it includes several species that may cause diarrhea. These species may be found in water, food and in the intestinal tract of chickens. This study investigated the presence of Campylobacter jejuni and Campylobacter coli in chicken abattoirs in São Paulo State, Brazil. A total of 288 samples of feces, feathers, scald water, evisceration water, chiller water, and the rinse water of eviscerated, not eviscerated and chilled carcasses were collected in six chicken abattoirs. Polymerase Chain Reaction (PCR) was performed in Campylobacter spp.-positive isolates using the gene HIP, specific for hippuricase enzyme from Campylobacter jejuni and aspartokinase gene, specific to detect Campylobacter coli. The percentage of positive isolates of Campylobacter jejuni was 4.9% (14/288). Isolation was greater in feces samples (22%, 8/36). One sample was positive for the species C. coli. In conclusion, the results indicate that it is necessary to improve quality control for Campylobacter spp. in chicken abattoirs.